The Presumed Principle of Confidentiality in Arbitration : A Challenging Balance Between the Presumed Principle of Confidentiality and Transparency in International Arbitration - Juronen, Kristina (fi=Turun yliopisto|en=University of Turku|, 2017)
International arbitration is one of the most important alternative dispute resolution methods in international law. It is valued especially for the reason that dispute resolution can be executed in a confidential and private manner. The principle of confidentiality has been thought to be automatically part of the arbitration since the very first arbitration cases. Hence, in this thesis, it was examined whether the principle of confidentiality can be assumed to be included in arbitration and whether it can be automatically part of arbitral proceedings. To addition, in this thesis were presented other potential advantages that the principle is bringing to arbitration and discussed the reasons of why this principle is really important. Different measures and matters that should be taken into account in order for the parties to maximise those mentioned benefits were also presented in this thesis. To the contrast, the negative aspects of the principle and the problems that it may bring to arbitration and other important matters that in specific circumstances outweigh the importance of the principle and override it were also discussed. In this thesis, such conclusion was reached that the mentioned principle cannot be absolutely taken for granted and assumed that the principle is applied to every case without limitations. The target audience of the research consists of different legal practitioners, legal scholars and possible students. The questions were approached by utilising different legal written material and source material in this thesis primarily consisted of different articles and literature that deals with the subject. The research method of legal dogmatics was applied to this work to approach the subject.